Agroecologia – um território em construção: considerações acerca das experiências agroecológicas nos Assentamentos Ireno Alves dos Santos e Marcos Freire no Município de Rio Bonito do Iguaçu/PR - Carvalho, Lisane (2017)
In this study, we tried to deal with reterritorialisation processes of settled peasants, triggered by agroecological practices, in the municipality of Rio Bonito do Iguaçu, in the Center-South Region of the state of Paraná. These are the Ireno Alves dos Santos and Marcos Freire settlements. We understand that the Green Revolution and the process of modernization of agriculture expropriated small farmers, deterritorializing them. Already the settlements are representative of a process of reterritorialization of these peasants. However, we believe that this reterritorialization should go beyond agroecological practices and less conventional ones, based on the dictates of modernization, since they were precisely those that contributed to the expropriation of peasants. To demonstrate the processes of reterritorialization of peasants, the territorial transformations evidenced by the dissemination of agroecological practices, the conflicts and disputes caused, the limits and advances of agroecology, the factors and the actors that contribute to the strategies of territorialization of the peasants, to the extent that we can verify the extent to which there is a territory of agroecology under construction, we use the theoretical reference of the geographers Claude Raffestin, Marcos Aurelio Saquet, Bernardo Mançano Fernandes and Márcio Freitas Eduardo. In this perspective the territorialization implies in the exercise of power of different actors on the space, as well as conflicts and disputes, mainly between agroecology and the technological package disseminated since the modernization of agriculture. From this comes the problem to be researched: How is the process of reterritorialization of the peasants being given through the territorialization of agroecology? In this way we try to describe and analyze the agroecological experiences that have been carried out in the mentioned settlements, pointing out their advances and challenges. Methodologically, this is a case study, based on semi-structured qualitative interviews conducted with 19 settled families who are developing agroecological practices and 6 representative entities / organizations. As results, we can contribute that the agroecology is characterized in a mechanism of reterritorialization of the peasants, allowing the permanence of the peasants in the settlements, guaranteeing greater autonomy of the peasants in relation to the internal and external conditions. Besides identifying that there is a territory of agroecology under construction, when settlers create new forms of work organization, when they fight for differentiated public policy, when they fight for the creation of cooperatives of production and commercialization, for housing, health, education and income security. However, we can observe that there are still many challenges to be overcome, such as obtaining certification; expansion of marketing channels; improving plant barriers and increasing the socio-environmental awareness of the majority of settled families that use the model of production of the Green Revolution.